High cyclic GMP-AMP synthase and stimulator of interferon genes in cholangiocarcinoma suggest their potential as targets for treatment - Han Ni Zin Myint; Paksiree Saranaruk; Natnicha Paungpan; Sakda Waraasawapati; Chawalit Pairojkul; Saowaluk Saisomboon; Nutsara Settha; Jatuporn Pattanachot; Seiji Okada; Wunchana Seubwai; Amnat Kitkhuandee; Kanlayanee Sawanyawisuth; et al. (PeerJ)
Background Cancer remains the leading cause of death worldwide. Chromosomal instability (CIN) is one hallmark of cancer. Micronuclei (MN) is an observable outcome of CIN. The role of cytosolic MNs or DNAs in activating an immune response via a cyclic guanosine monophosphate–adenosine monophosphate (GMP-AMP) synthase (cGAS)-a stimulator of interferon genes (STING) signaling cascade is established. However, the information regarding the cGAS-STING pathway in cholangiocarcinoma (CCA) is limited. This study aimed to determine cGAS-STING-related molecules in CCA and reveal their clinical importance. Methods MNs in CCA cell lines were demonstrated by nuclear staining and cGAS, STING, nuclear factor kappa B (NF-κB) p65 were determined by Western blot analysis. Expressions of cGAS-STING-related mRNAs in gastrointestinal cancers were analyzed using Gene Expression Profiling Interactive Analysis (GEPIA) based on The Cancer Genome Atlas (TCGA) database. The expressions of cGAS, STING, and NF-κB p65 in clinical CCA samples were determined by immunohistochemistry (IHC) staining. The survival analyses were conducted using Kaplan-Meier survival analysis with a log-rank test, and the correlations between the targeted protein expression levels and clinical parameters were examined using Pearson’s Chi-square test. Furthermore, the Cox proportional hazard regression model was utilized for multivariate analysis. The expression levels of CGAS, STING, and RELA were analyzed using two public datasets of CCA. The relationship between key mRNAs and related immune cell infiltration was analyzed using the Tumor Immune Estimation Resource (TIMER). Results MNs generated during cytokinesis were demonstrated in the CCA cell lines and were positively correlated to STING level. GEPIA analysis revealed that members of the cGAS-STING pathway were significantly increased in GI cancers, particularly CCA and pancreatic cancer. IHC confirmed high cGAS and STING in CCA tissues, while NF-κB p65 showed variable expression. High NF-κB p65 was correlated with shorter patient survival, and larger tumor size. High NF-κB p65 contributed to an increased hazard ratio of 1.679 (95% confidence interval [1.074–2.626]). TIMER analysis demonstrated CGAS and STING were positively correlated with neutrophil, γδ T cell, and CD8+ T cell infiltration, while STING and RELA were associated with higher B cell infiltration. High CGAS, STING, and RELA were related to increased myeloid dendritic cell infiltration. Conclusions The high number of MNs in CCA cell lines emphasize their importance. Elevated cGAS, STING, and NF-κB p65 in CCA tissues highlight the significance of this pathway. While cGAS and STING showed no direct prognostic value, NF-κB p65 was identified as a prognostic predictor. Altogether, the opportunity of cGAS and STING targeting for CCA treatment and the predictive character of NF-κB p65 are proposed, and further exploration is recommended.